A yield function for granular materials based on microstructures. Issue 4 (15th June 2015) - Y.T. Feng, Professor Xikui Li, Professor Yuangqiang Tan and Professor Shunying Ji, Professor; Liu, Sihong; Wang, Zijian; Wang, Yishu; Wang, Liujiang; Fu, Zhongzhi
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose a new yield function for granular materials based on microstructures. Design/methodology/approach – A biaxial compression test on granular materials under different stress paths is numerically simulated by distinct element method. A microstructure parameter S that considers both the arrangement of granular particles and the inter-particle contact forces is proposed. The evolution of the microstructure parameter S under the simulated stress paths is analyzed, from which a yield function for granular materials is derived. The way of determining the two parameters involved in the yield function is proposed. Findings – The new yield function is calibrated using the test data of one sand and two rockfill materials. The shape of the new yield surface is similar to that of the Cam-clay model. Originality/value – The paper proposes a microstructure parameter S, which considers both the arrangement of granular particles and the inter-particle contact forces. From the evolution of S, a yield function for granular materials is derived. The proposed yield function has a simple structure and the parameters are easy to be determined, leading to a feasible realization of engineering application.